The Theory of Price / Fourth Edition - Stigler George J (Macmillan Publishing Company, 1987)
Introduction to Economic Analysis, Prices and the Enterprise Economy, Consumer Behavior, The Theory of Utility, Pricing with Limited Supplies, The Supplies of Productive Services, Costs and Production, Production: Diminishing Returns, Production: Returns to Scale, Additional Topics in Production and Costs, The General Theory of Competitive Prices, The Theory of Monopoly, Oligopoly and Cartels and Mergers, The Economics of Information, The Demand for Productive Services, Rents and Quasi-Rents, Wage Theory, The Size Distribution of Income, Capital and Interest, The Economy and the State, Appendices, Index.